2022
DOI: 10.1093/ced/llac070
|View full text |Cite
|
Sign up to set email alerts
|

The impact of using a multistrain probiotic supplement on gastrointestinal function in children and adolescents with severe recessive dystrophic epidermolysis bullosa

Abstract: Background Children and adolescents with severe recessive dystrophic epidermolysis bullosa (RDEB-S) often have severe constipation in addition to gastrointestinal dysbiosis, due to frequent antibiotic use and reduced oral diet. Constipation is treated with long-term use of high daily doses of macrogol gel (Movicol Paediatric PlainTM or LaxidoTM). Constipation is refractory to increases in fibre and fluids, and impacts severely on quality of life. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
0
0
Order By: Relevance
“…The results showed that the probiotics could relieve the constipation induced by loperamide. Multi-strain probiotic combinations have undoubtedly become a research hotspot [22,23]. In addition, there is much information about the improvement of multi-strain probiotics in non-alcoholic fatty liver disease [24], severe major depressive disorder, and accompanying gastrointestinal syndromes [25].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the probiotics could relieve the constipation induced by loperamide. Multi-strain probiotic combinations have undoubtedly become a research hotspot [22,23]. In addition, there is much information about the improvement of multi-strain probiotics in non-alcoholic fatty liver disease [24], severe major depressive disorder, and accompanying gastrointestinal syndromes [25].…”
Section: Introductionmentioning
confidence: 99%